Neural circuits and emotional processing in rapid eye movement sleep - Chang, Liu-Yan; Wang, Yue-Qian; Li, Zhe; Zhang, Yang; Huang, Zhi-Li; Yang, Su-Rong (Frontiers in Psychiatry, 2025)
Mammalian sleep consists of non-rapid eye movement sleep (NREMS) and rapid eye movement sleep (REMS), accounting for approximately 75% and 25% of total sleep, respectively. REMS is characterized by low-amplitude and high-frequency theta oscillations in the brain, muscle atonia, intermittent muscle twitches, rapid eye movements, and rapid breathing. Although relative brief in duration, REMS is evolutionarily conserved across species. Notably, REMS plays a critical role in emotion regulation and its dysregulation has been closely associated with neuropsychiatric disorders such as post-traumatic stress disorder (PTSD) and depression. However, the precise neural mechanisms that initiate and terminate REMS, as well as the exact pathophysiological relationships between REMS and psychiatric conditions, remain poorly understood. In recent years, research on the circuitry and functional roles of REMS has advanced considerably, with growing evidence implicating several cortical and brainstem regions in its regulation. Here, we review the mechanisms of mammalian REMS in terms of brain anatomy and neural circuits, which constitute highly distributed networks spanning the cortex, brain stem, hypothalamus, and other regions. We also summarize the role of REMS in negative emotion processing. Finally, we propose key open questions that need to be addressed in future studies.